Bài 3:
a: Ta có: \(P=\left(a^2-2a+4\right)\left(a+2\right)-a^3+\left(a+3\right)\left(a-3\right)-a^2-18\)
\(=a^3+8-a^3+a^2-9-a^2-18\)
\(=-19\)
b: Ta có: \(Q=\left(x-5\right)\left(2x+3\right)-2x\left(x-3\right)+x+7\)
\(=2x^2+3x-10x-15-2x^2+6x+x+7\)
=-8
Bài 1:
a: Ta có: \(\left(x+3\right)\left(x-4\right)\)
\(=x^2-4x+3x-12\)
\(=x^2-x-12\)
b: Ta có: \(\left(x-4\right)\left(x^2+4x+16\right)\)
\(=x^3+4x^2+16x-4x^2-16x-64\)
\(=x^3-64\)
c: Ta có: \(\left(xy^2-1\right)\left(x^2y+5\right)\)
\(=x^3y^3+5xy^2-x^2y-5\)
d: Ta có: \(x\left(x-\dfrac{1}{2}\right)\left(x+\dfrac{1}{2}\right)\)
\(=x\left(x^2-\dfrac{1}{4}\right)\)
\(=x^3-\dfrac{1}{4}x\)
e: Ta có: \(\left(\dfrac{1}{2}x-1\right)\left(2x-3\right)\)
\(=x^2-\dfrac{3}{2}x-2x+3\)
\(=x^2-\dfrac{7}{2}x+3\)
f: Ta có: \(\left(x-1\right)\left(x+1\right)\left(2x+2\right)\)
\(=\left(x^2-1\right)\left(2x+2\right)\)
\(=2x^3+2x^2-2x-2\)
Bài 2:
a: Ta có: \(\left(x+3\right)\left(2x-1\right)-2x\left(x+4\right)-5x\)
\(=2x^2-x+6x-3-2x^2-8x-5x\)
\(=-8x-3\)
b: Ta có: \(\left(1-3x\right)\left(x-2\right)-\left(x+4\right)\left(2x+3\right)\)
\(=x-2-3x^2+6x-\left(2x^2+3x+8x+12\right)\)
\(=-3x^2+7x-2-2x^2-11x-12\)
\(=-5x^2-4x-14\)
c: Ta có: \(\left(a-b\right)\left(a^2+ab+b^2\right)-\left(a+b\right)\left(a^2-ab+b^2\right)\)
\(=a^3-b^3-\left(a^3+b^3\right)\)
\(=a^3-b^3-a^3-b^3\)
\(=-2b^3\)
Bài 4:
a: Ta có: \(\left(x^2+2x+4\right)\left(2-x\right)+x\left(x-3\right)\left(x+4\right)-x^2+24=0\)
\(\Leftrightarrow2-x^3+x\left(x^2+x-12\right)-x^2+24=0\)
\(\Leftrightarrow-x^3-x^2+26+x^3+x^2-12x=0\)
\(\Leftrightarrow12x=26\)
hay \(x=\dfrac{13}{6}\)
b: Ta có: \(\left(12x-5\right)\left(4x-1\right)+\left(3x-7\right)\left(1-16x\right)=81\)
\(\Leftrightarrow48x^2-12x-20x+5+3x-48x^2-7+112x=81\)
\(\Leftrightarrow83x=83\)
hay x=1